Synthesis, Crystal Structure, and Properties of a New Zinc(II) Coordination Polymer With Mixed 4, 4′-biphenyldisulfonic Acid and N-Donor Ligands. Issue 12 (1st December 2016) - Lermontova, Elmira Kh.; Yang, Guo-Ping; Wang, Xun-Ming; Wang, Yao-Yu; Shi, Qi-Zhen
Abstract : A new zinc(II) coordination polymer, namely [Zn(bipy)2 (H2 O)4 ] n · n (dsba) (1), has been synthesized by the mixed 4, 4′-biphenyldisulfonic acid (H2 dsba) and 4, 4′-bipyridine (bipy) ligands with Zinc(II) salt under the common solution evaporation method. The results of the X-ray crystal diffraction analysis show that complex 1 belongs to the monoclinic system with P21 /c space group. The unit cell constants of complex 1 are a = 9.2579 Å, b = 12.2016 Å, c = 14.447 Å, α = γ = 90˚, β = 93.476˚. Complex 1 exhibits a three-dimensional supramolecular network based on the discrete structure by utilizing various H-bonded interactions. In addition, the properties of complex 1, such as the elemental analysis, FT-IR spectroscopy, X-ray powder diffraction, and fluorescence spectroscopy were also characterized and are discussed in detailed.